Stable carbon isotope ratios of bulk organic matters from sediment core PS51/154-11 - Tsai-Wen Lin; Tommaso Tesi; Gesine Mollenhauer (PANGAEA, 2025)
The data include stable carbon isotope ratios (δ13C) from bulk organic matter in core PS51/154-11. Freeze-dried, homogenized sediments were acidified with 1.5 M HCl in silver boats and then dried in an oven at 55 C. δ13C values were measured using a Thermo Scientific FLASH 2000 CHNS Analyser coupled with a Thermo DeltaQ IRMS via CONFLO IV.
In: Lin, Tsai-Wen; Tesi, Tommaso; Hefter, Jens; Grotheer, Hendrik; Wollenburg, Jutta Erika; Mollenhauer, Gesine (2025): Bulk organic matter δ13C, biomarker, and microfossil radiocarbon data of cores PS51/154-11 and PS51/159-10 from the Laptev Sea, Arctic Ocean [dataset bundled publication]. PANGAEA, https://doi.pangaea.de/10.1594/PANGAEA.980076 (DOI registration in progress)